Gymnastics injury incidence during the 2008, 2012 and 2016 Olympic Games: analysis of prospectively collected surveillance data from 963 registered gymnasts during Olympic Games. Issue 7 (14th October 2017) - Edouard, Pascal; Steffen, Kathrin; Junge, Astrid; Leglise, Michel; Soligard, Torbjørn; Engebretsen, Lars
Abstract : Objective: To determine the incidence and characteristics of injuries in female and male gymnastics disciplines (artistic, rhythmic and trampoline) during three Olympic Games with a view to ultimately improving injury prevention. Methods: The National Olympic Committee's head physicians and the medical teams of the Local Organising Committee of the Olympic Games reported daily the occurrence (or non-occurrence) of newly sustained injuries in artistic, rhythmic and trampoline gymnastics on a standardised report form during the 2008, 2012 and 2016 Summer Olympic Games. Results: During the three Olympic Games, 81 injuries were reported in a total of 963 registered gymnasts, corresponding to an incidence of 84 injuries (95% CI 67 to 102) per 1000 registered gymnasts, with no difference in injury incidence between female and male gymnasts. Thirty-eight per cent of injuries led to time-loss from sport. The most frequent injury location and injury type were the ankle (22%) and sprain (35%), respectively. The most common diagnosis was ankle sprain (14% of all injuries and 23% of time-loss injuries). The injury incidence was highest in female (107±35) and male artistic gymnastics (83±32), followed by female rhythmic gymnastics (73±30), and lower in male (63±69) and female (43±43) trampoline gymnastics. Conclusions: Research should focus on preventing injuries in artistic gymnastics and of the condition of ankle sprain. Injury surveillance studies should be continued during major championships and throughout the entire competitive season as the Olympic Games provides only a snapshot (although an important one).